Inclusion criteria update for the rat intraluminal ischaemic model for preclinical studies - Héctor Fernández-Susavila; Ramón Iglesias-Rey; Antonio Dopico-López; María Pérez-Mato; Tomás Sobrino; José Castillo; Francisco Campos (The Company of Biologists, 2017)
Proper occlusion of the medial cerebral artery, as determined by laser Doppler monitoring, during cerebral ischaemia in rat models is an important inclusion criterion in experimental studies. However, successful occlusion of the artery does not always guarantee a reproducible infarct volume, which is crucial for validating the efficacy of new protective drugs. In a rat intraluminal ischaemic model, laser Doppler monitoring alone was compared with laser Doppler monitoring in combination with magnetic resonance angiography (MRA) and diffusion-weighted imaging (DWI). Twenty-eight animals showed successful occlusion and reperfusion determined with Doppler monitoring, with an infarct size at 24 h of 16.7±11.5% (determined as ischaemic damage with respect to the ipsilateral hemisphere volume). However, when arterial occlusion and infarct damage were analysed in these animals using MRA and DWI, respectively, 15 animals were excluded and only 13 animals were included, with an infarct size at 24 h of 21.6±6.1%, showing a variability in the infarct size significantly lower (P<0.05, F-test) than that obtained with Doppler monitoring alone. We also observed that blocking of the pterygopalatine artery (a maxillary artery that is usually occluded in the intraluminal ischaemic model) was not relevant for this model, at least in terms of infarct variability. These results show that laser Doppler monitoring is a necessary procedure, but not sufficient to guarantee a reproducible infarct volume, in a rat ischaemic model. Therefore, laser Doppler monitoring in combination with DWI and MRA represents a reliable inclusion protocol during ischaemic surgery for the analysis of new protective drugs.